Is there rent sharing in developing countries? matched-panel evidence from Brazil - Pedro Silva Martins; Luiz A. Esteves (Institute for the Study of Labor (IZA), 2006)
We provide evidence about the determinants of the wage structures of developing countries by examining the case of Brazil. Our specific question is whether Brazil's dramatic income and wage differentials can be explained by the division of rents between firms and their employees, unlike in competitive labour markets. Using detailed individual-level matched panel data, covering a large share of manufacturing firms and more than 30 million workers between 1997 and 2002, we consider the endogeneity of profits, by adopting different measures of profits and different instruments and by controlling for spell fixed effects. Our results, robust to different specifications and tests, indicate no evidence of rent sharing. This conclusion contrasts with findings for most developed countries, even those with flexible labour markets. Possible explanations for the lack of rent sharing include the weakness of labour-market institutions, the high levels of worker turnover and the macroeconomic instability faced by the country.
Keywords: 330